Effectiveness of early heparin therapy on outcomes in critically ill patients with sepsis-induced coagulopathy - Huang, Jia-Jia; Zou, Zhi-Ye; Zhou, Zhi-Peng; Liu, Yan; Yang, Zhen-Jia; Zhang, Jing-Jing; Luan, Ying-Yi; Yao, Yong-Ming; Wu, Ming (Frontiers in Pharmacology, 2023)
Background: This study aimed to investigate whether early unfractionated heparin (UFH) administration provides a survival advantage for patients with sepsis-induced coagulopathy (SIC). Methods: Patients hospitalized with sepsis-induced coagulopathy from the Medical Information Mart for Intensive Care (MIMIC)-IV database were identified. Patients were divided into two groups, who received unfractionated heparin (UFH) subcutaneously within 24 h after intensive care unit (ICU) admission, and the control group, who received not. The primary endpoint was intensive care unit mortality, the secondary outcomes were 7, 14, and 28-day and hospital mortality. Propensity score matching (PSM) the marginal structural Cox model (MSCM) and E-value analysis were used to account for baseline differences, time-varying and unmeasured confounding factors. Results: A total of 3,377 patients with sepsis-induced coagulopathy were enrolled in the study, of which 815 in unfractionated heparin group and 2,562 in control group. There was significant effect on primary and secondary outcomes with unfractionated heparin after propensity score matching (intensive care unit mortality, hazard ratio [HR] 0.69, 95% confidence interval [CI] 0.52–0.92; 7-day, HR 0.70, 95% CI 0.49–0.99; 14-day, HR 0.68.95% CI 0.50–0.92; 28-day, HR 0.72, 95% CI 0.54–0.96; hospital mortality, HR 0.74, 95% CI 0.57–0.96), marginal structural Cox model manifested unfractionated heparin associated with decreased intensive care unit mortality in all populations (HR 0.64, 95% CI 0.49–0.84), and stratification with the marginal structural Cox model indicated analysis further indicated the survival advantage only among patients with an sepsis-induced coagulopathy score of 4 (HR 0.56, 95% CI 0.38–0.81). Further analysis showed that treatment with 6,250–13750 IU/day of unfractionated heparin associated with a decreased risk of intensive care unit mortality. Similar results were replicated in subgroup analysis with propensity score matching only for patients with an sepsis-induced coagulopathy score of 4 (intensive care unit mortality, HR 0.51, 95% CI 0.34–0.76). Conclusion: This study found early unfractionated heparin therapy to patients with sepsis-induced coagulopathy appears to be associated with improved outcomes. Subgroup analysis further demonstrates heparin therapy decreased intensive care unit mortality primarily in patients only with SIC score of 4.